Vulnerability and Resilience: A Short Introduction to the Challenges of Administrative Law and Public Governance in the Age of Uncertainty - Pinto, João Vilas Boas (Public Governance, Administration and Finances Law Review, 2024)
This text, aiming to contribute to the reflection of the main challenges faced by today's Societies, seeks, in essence, to draw attention to the importance of deepening the relations between Administrative Law and Public Governance, reflecting, for this purpose, on a framework of tension between a Vulnerable Society and the need for its resilient transformation, associated with disruptive phenomena such as the pandemic, globalisation and the digital transition. In this sense, the exercise that we propose here, necessarily of an introductory nature, involves, at first, an approximation to the concept of "vulnerability", seeking to direct it to the legal level, and in particular seeking to cut it in the spectrum of Administrative Law, so that, at a subsequent moment, it becomes possible to point out the need for greater responsiveness – and, so too, "resilience" – on the part of public authorities, in an appeal to a dynamic but complex intersection between public policies and instruments of democratic governance and legal regulation, based on a matrix that privileges the dignity of the human person and fundamental constitutional values.